Reflections on the reform for the expansion and strengthening of the judiciary and the prosecution service - Jiménez Martín, Jorge (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
In these lines we will analyze and comment on the Preliminary Draft Organic Law which seeks to amend Organic Law 6/1985, of July 1, 1985, on the Judiciary, and Law 50/1981, of December 30, 1981, which regulates the Organic Statute of the Public Prosecutor’s Office, for the expansion and strengthening of the Judiciary and Prosecutor’s office. The aims are extremely pretentious for the limited reform that is being carried out, affecting points that may be merely accidental but that have special significance in the objectives to be achieved and in the model of Judiciary and Prosecutor’s office that is intended to be designed.